2019
DOI: 10.1111/ijau.12164
|View full text |Cite
|
Sign up to set email alerts
|

Clash of corporate governance logics obscuring auditor independence

Abstract: Audit committees are regarded by regulators as beneficial for improving audit independence and are hence globally enforced. This study aligns with research that questions whether audit committees function well in nations that differ from the Anglo‐Saxon model. The aim of the study is to examine if the auditor and audit committee relationship conforms with a Swedish or Anglo‐Saxon logic, and to analyze the impact on auditor independence. A critical discourse analysis is undertaken on corporate governance report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Audit committees and corporate governance have a perceived alignment because they focus on internal audit and external audit reporting. By matching the functions of an audit committee with corporate governance in the literature reviews, The study found the quality of an audit committee attributes research on corporate governance is positive when associated with firm performance (Kooli & Abadli, 2021;Kooli, 2019;Alander, 2019;Gebrayel et al, 2018;Brown, Popova, & Velina, 2016;Samaha, Khlif, & Hussainey, 2015;Al-Najjr & Abed, 2015).…”
Section: Identified Trend Themes Of the Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Audit committees and corporate governance have a perceived alignment because they focus on internal audit and external audit reporting. By matching the functions of an audit committee with corporate governance in the literature reviews, The study found the quality of an audit committee attributes research on corporate governance is positive when associated with firm performance (Kooli & Abadli, 2021;Kooli, 2019;Alander, 2019;Gebrayel et al, 2018;Brown, Popova, & Velina, 2016;Samaha, Khlif, & Hussainey, 2015;Al-Najjr & Abed, 2015).…”
Section: Identified Trend Themes Of the Literature Reviewmentioning
confidence: 99%
“…The review has evidenced empirical studies (e.g. Kooli & Abadli, 2021;Kooli, 2019;Alander, 2019;Gebrayel et al, 2018;Brown, Popova, & Velina, 2016;Samaha, Khlif, & Hussainey, 2015;Al-Najjr & Abed, 2015). Despite the prior empirical studies of this scientific field there still remains further studies to provide insight of their relative functions in both developed and developing economies.…”
Section:  Impact Of Internal External and Audit Committee On Corpora...mentioning
confidence: 99%
“…Second, previous institutional logic studies of accounting firms are within Anglo-American jurisdictions, which differ substantially from a Continental European and Scandinavian context. Despite the globalizing influence of the large audit firms, auditors are individuals and it is possible that institutional logics vary in different countries (Lander et al, 2013;Alander, 2019). We thus contribute by examining institutional logics in the European context, specifically Denmark.…”
Section: Introductionmentioning
confidence: 99%